2017
DOI: 10.1159/000485764
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib Down-Regulates the Hypoxia-Induced Expression of HIF-1α and VEGF Through the PI3K/AKT Pathway in Retinal Pigment Epithelial Cells

Abstract: Background/Aims: The goal of this study was to detect the expression of hypoxia-inducible factor 1α (HIF-1α) and vascular endothelial growth factor (VEGF) in human retinal pigmented epithelial (RPE) cells treated with celecoxib, a selective cyclooxygenase-2 (COX-2) inhibitor, under hypoxic and normoxic conditions and to explore the signaling mechanism involved in regulating the hypoxia-induced expression of HIF-1α and VEGF in RPE cells. Methods: D407 cells were cultured in normoxic or hypoxic conditions, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
0
20
1
Order By: Relevance
“…Our study highlights that the capacity of celecoxib to aid repair in pAEC from children with wheeze is independent of COX2 inhibition. Unlike our findings, previous work in the oncology literature has suggested that celecoxib treatment of cancer cell lines may inhibit PI3K/Akt signaling at high micromolar concentrations (44,45). This discrepancy may highlight dose-dependent and cell-specific responses to celecoxib treatment in vitro.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study highlights that the capacity of celecoxib to aid repair in pAEC from children with wheeze is independent of COX2 inhibition. Unlike our findings, previous work in the oncology literature has suggested that celecoxib treatment of cancer cell lines may inhibit PI3K/Akt signaling at high micromolar concentrations (44,45). This discrepancy may highlight dose-dependent and cell-specific responses to celecoxib treatment in vitro.…”
Section: Discussioncontrasting
confidence: 99%
“…The RPE, a monolayer of pigmented cells located between the nerve retina and Bruch’s membrane, is an important partner for the fit of the retina, and disturbance of the RPE may ultimately lead to retinal damage and disease. Various studies have investigated the relationship and underlying mechanism between the RPE and ocular diseases [19-21]. The RPE also participates in the pathogenesis of PVR.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the risk of intravitreal infection is much higher and some patients also respond poorly to anti-VEGF treatments [42] .Thus, identification of novel targets that play important roles in retinal neovascularization is urgently needed for those not responsible for anti-VEGF therapy [43] . Studies also demonstrated that celecoxib could inhibit the expression of VEGF and neovascularization growth in retinal pigment epithelial cells and the effect was mediated through a PI3K/AKT-dependent manner [44] and abrogating of VEGF significantly reduced the risk of developing to PDR in type 2 diabetes patients [45] .…”
Section: Discussionmentioning
confidence: 98%